2020
DOI: 10.1016/j.omtn.2020.08.033
|View full text |Cite
|
Sign up to set email alerts
|

miR-301a-PTEN-AKT Signaling Induces Cardiomyocyte Proliferation and Promotes Cardiac Repair Post-MI

Abstract: Adult hearts are hard to recover after cardiac injury due to the limited proliferative ability of cardiomyocytes. Emerging evidence indicates the induction of cell cycle reentry of cardiomyocytes by special treatment or stimulation, which offers adult heart regenerative potential. Herein, a microRNA (miRNA) screening in cardiomyocytes identified miR-301a enriched specially in the neonatal cardiomyocytes from rats and mice. Overexpression of miR-301a in primary neonatal cardiomyocytes and H9C2 cells induced G … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 51 publications
1
30
0
Order By: Relevance
“…During the development of cardiac hypertrophy, PTEN is modulated and plays a vital role. Suppression of PTEN by miR‐301a could promote cardiomyocytes proliferation 30 . Tripartite motif 10 (TRIM10) promoted ubiquitination of PTEN, consequently resulting in its proteasomal degradation and activation of hypertrophic signalling 31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the development of cardiac hypertrophy, PTEN is modulated and plays a vital role. Suppression of PTEN by miR‐301a could promote cardiomyocytes proliferation 30 . Tripartite motif 10 (TRIM10) promoted ubiquitination of PTEN, consequently resulting in its proteasomal degradation and activation of hypertrophic signalling 31 .…”
Section: Discussionmentioning
confidence: 99%
“…PTEN expression is regulated by many transcription factors such as the zinc-finger transcription factor sal-like protein 416 and the transacting EMT transcription factor SNAIL (also known as SNAI1)17 as well as microRNAs such as miR-19 in Cowden and leukaemia disease,18,19 the miR-17-92 cluster in lymphoproliferative disease,20 miR-21 in multiple cancers and metabolic and inflammatory diseases 21,22. PTEN function can be modulated by its interacting proteins such as Na + /H PTEN is modulated and plays a vital role.Suppression of PTEN by miR-301a could promote cardiomyocytes proliferation 30. Tripartite motif 10 (TRIM10) promoted ubiquitination of PTEN, consequently resulting in its proteasomal degradation and activation of hypertrophic signalling 31.…”
mentioning
confidence: 99%
“…More specifically, miR-199a-3p downregulates YAP inhibitory kinase, TAOK1, and the E3 ubiquitin ligase, β-TrCP, to inhibit YAP degradation, and also represses Cofilin2 to maintain YAP nuclear localization [73]. PTEN/PI3K/AKT is another signal transduction pathway that is activated by miR-301a to promote cardiomyocyte re-entry into the cell cycle; miR-301a suppresses PTEN to activate AKT and induce expression of cell cycle genes such as cyclin D1, in cardiac myocytes [50]. Other miRNAs have been reported to promote cell cycle progression in cardiomyocytes by targeting the TBX1/JAK2/STAT1 pathway [74], the NFkB pathway [75], or signaling molecules such as the cell cycle inhibitors Wee1 [76] and Bim [77], among others [78,79].…”
Section: Selective Induction/inhibition Of Gene Expression Can Induce Cell Cycle Re-activation In Cardiac Myocytesmentioning
confidence: 99%
“…Phosphatase and tensin homolog (PTEN) is a very commonly mutated tumor suppressor gene in human cancers, including HCC. 26 , 27 , 28 , 29 Accumulating evidence has shed light on PTEN activity, which can be regulated by mutations, epigenetic silencing, abnormal protein, transcriptional inhibition, localization, and posttranslational modification. 30 , 31 , 32 At the same time, some data have indicated that decreased PTEN expression is a common event in HCC and is associated with disease stage, tumor grade and size, and increased expression of tumor markers.…”
Section: Introductionmentioning
confidence: 99%